Impact of Workshop Experiences on Building Finishing Skills of Building Technology Education Students in Public University in Anambra State - Ogunmola, Abiodun Emmanuel; Agbo, Nnaemeka Martin; Ifeacho, Victor Chinedu (Journal of Research in Industrial Technology and Educational Studies, 2025)
The study assessed the impact of workshop experiences on building finishing skills of building technology education students in public university, Awka, Anambra State. Two research questions guided the study while two hypotheses were tested at 0.05 alpha level. The population consisted of 54 building technology education students. Census sampling technique was used. Instrument for data collection was a structured questionnaire. Out of the 54 questionnaires distributed, 45 copies were retrieved which represented 83.3 percent retrieval. The data were analyzed using simple linear regression. The results showed no significant impact of workshop experiences on tiling and painting skills, with p-values exceeding the 0.05 significance level. This indicated that workshop experiences, as currently offered to the students, do not contribute meaningfully to the skills development of students of building technology education. Based on these findings, it was recommended that workshops should be restructured to emphasize practical, hands-on training, with modern tools and equipment provided.